Learning coronary artery calcium scoring in coronary CTA from non-contrast CT using unsupervised domain adaptation - Zhai, Zhiwei; van Velzen, Sanne G. M.; Lessmann, Nikolas; Planken, Nils; Leiner, Tim; Išgum, Ivana (Frontiers in Cardiovascular Medicine, 2022)
Deep learning methods have demonstrated ability to perform accurate coronary artery calcium (CAC) scoring. However, these methods require large and representative training data hampering applicability to diverse CT scans showing the heart and the coronary arteries. Training methods that accurately score CAC in cross-domain settings remains challenging. To address this, we present an unsupervised domain adaptation method that learns to perform CAC scoring in coronary CT angiography (CCTA) from non-contrast CT (NCCT). To address the domain shift between NCCT (source) domain and CCTA (target) domain, feature distributions are aligned between two domains using adversarial learning. A CAC scoring convolutional neural network is divided into a feature generator that maps input images to features in the latent space and a classifier that estimates predictions from the extracted features. For the adversarial learning, a discriminator is used to distinguish the features between source and target domains. Hence, the feature generator aims to extract features with aligned distributions to fool the discriminator. The network is trained with adversarial loss as the objective function and a classification loss on source domain as a constraint for adversarial learning. In the experiments, three data sets were used. The network is trained with 1,687 labeled chest NCCT scans from the National Lung Screening Trial. Furthermore, 200 labeled cardiac NCCT scans and 200 unlabeled CCTA scans were used to train the generator and the discriminator for unsupervised domain adaptation. Finally, a data set containing 313 manually labeled CCTA scans was used for testing. Directly applying the CAC scoring network pretrained on NCCT to CCTA led to a sensitivity of 0.41 and an average false positive volume 140 mm3 scan. The proposed method improved the sensitivity to 0.80 and reduced average false positive volume of 20 mm3 scan. The results indicate that unsupervised domain adaptation approach enables automatic CAC scoring in contrast enhanced CT while learning from a large and diverse set of CT scans without contrast. This may allow for better utilization of the existing annotated data sets and extend the applicability of automatic CAC scoring to diverse CT scans without the need for additional manual annotations.